Literature Rhetoric of the Phu Thai People - Thattham, Wipat (Journal of Graduate MCU KhonKaen Campus, 2022)
Abstract Thai society has a culture that has been dubbed as "culture of phu thai" that creates artistic beauty, culture, customs and way of life from generation to generation and is a legacy to the present. The phu thai people have ancestors that originated in the area of fédération thaï which was an area in southern China about 2,700 years ago. The phu thai people have migrated to thailand many times and have settled in both the northeastern and central provinces. The phu thai people have a simple way of life. have sufficiency phu thai women do housework, grow vegetables, raise animals, and are unique in weaving cloth for their own use. and phu thai man will be the leader in providing family support, hunting, and making tools and utensils for everyday life in the wicker type using natural materials. at present, the phu thai people still maintaining the traditions that have been seen in the old phu thai people. as for teenagers, there has been a change in the globalization. The belief of the phu thai people is to believe in spirits, spirits, ancestors, sacred things naturally. There are rituals related to beliefs. phu thai people live in a large family in the same house. It is a group of working people who are diligent, thrifty, can work in many professions. Knowledge and understanding and strength in governance They have beautiful faces, good complexions, and are hospitable and friendly in welcoming their guests to the point of being mentioned have good understanding and strength in governance They have beautiful faces, good complexions, and are hospitable and friendly in welcoming their guests to the point of being mentioned. The phu thai renu nakhon dance is a traditional dance that has been continually passed on from ancestors. This phu thai dance is considered a unique cultural art of the phu thai renu nakhon tribe. It is considered that the phu thai dance is a symbol of nakhon phanom province. at the present, the ministry of education has included subjects phu thai renu nakhon dance into the course for both primary and secondary students have practiced studying, especially students studying in educational institutions within the district of renu nakhon. As for the identity, identity, arts and culture of the race will be reflected through the literature. The refined and beautiful rhetoric of the phu thai people.